PESANTREN AND ITS FUNCTION IN IMPROVING THE WORSHIP OF THE VILLAGE COMMUNITY - Setiawati, Rini; Mubasit, Mubasit; Mawardi, Muhammad; Cahyadi, Ashadi (Universitas Islam Negeri Raden Intan Lampung, 2023)
The research aims to examine the function of Baitul Qur'an Student Boarding School in improving community worship in Pekon Podosari, Pringsewu Regency Lampung. This research uses a qualitative method, which is research that is This research uses qualitative methods, which are used to find data derived from field data, as well as data from interviews, documentation, and observations obtained through the process of recording what it is about objective conditions, namely methods used to make generalizations, and then analyzed using descriptive analysis methods. The results of this study indicate that the function of the Baitul Qur'an Student Boarding School is to provide a place for the community to attend Friday night recitation and a place where children can learn to read the Qur'an and memorize the Qur'an. The increase in community worship as a result of the da'wah activities of the Baitul Qur'an student boarding school in Podosari Pringsewu Village is that the community's knowledge about the practice of worship increases with the addition of recitation material, namely religious lectures/Tausyiah and questions, and answers, and the recitation is routinely held at least one time in one week every Friday night, increasing the ability of community children to read the Qur'an and memorize the Qur'an.